ANOMALY IN ‘MUHURTA TIME’ OF TIRUMALA VENKATESWARA SWĀMIVĀRI BRAHMOTSAVAM - Rao, Y. V. Subba (International Journal of Research -GRANTHAALAYAH, 2021)
The starting time or commencement of , an annual festival, at the Lord Venkateswara Temple at , celebrated by (TTD) is a total deviation from injunction whereas an additional festival celebrated in an once in three years comes unaware in total conformity with prescription of the ‘ time” for the commencement of this most sacred and important temple ritual. The rectification of the deviation occurring due to the erroneous astronomical positions of planets, the Sun and the Moon, in the Luni-Solar Indian almanac (TTD ) is discussed here with a suggestion of rectification of in the “ Time” for the of the Planet and all life living on it.